Philosophy of Race - Zack, Naomi (Springer, 2018)
Many academic philosophers who are generally interested in social justice issues pertaining to racial and ethnic minority groups still do not clearly distinguish between Philosophy of Race and African American philosophy. And in American public discourse, African Americans are the primary racial subject. But the existence of other nonwhite groups in the United States and throughout the world calls for a shared discourse about the plurality of racial and ethnic injustices endured and resisted. It is therefore now useful to consider Philosophy of Race as a distinct academic subfield. Philosophy of Race has primarily emerged from African American philosophy, which not only carries an awareness of injustices suffered by other groups but has since the 1970s raised issues that redound to traditional ethics and political and social philosophy.
An Introduction